2022
DOI: 10.3390/ijerph191911908
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of a Community-Based Peer-Led Wheelchair Skills Training on Satisfaction with Participation in Children and Adolescents with Cerebral Palsy and Spina Bifida: A Pilot Study

Abstract: Background: Peer-led approaches improve satisfaction with participation, wheelchair skills and wheelchair use self-efficacy in adults, but the evidence is limited in children. This pilot study aimed to explore the influence of community-based, peer-led, group wheelchair training program (i.e., Seating To Go) on satisfaction with participation (primary outcome), wheelchair skills, and wheelchair use self-efficacy in children and adolescents with cerebral palsy and spina bifida. Methods: A single group pre-post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The team chose to conduct an intensive dance camp because several studies suggest that intensive rehabilitative approaches (with intense repetitions) are associated with improved neuroplasticity and global motor function over the long term [18,39,40]. Even though the most optimal duration and frequency remain unknown for young people, some research suggests that condensed training may not be the most suitable option to promote skills development in this population and that, consequently, frequent and shorter training sessions distributed over a longer period of time appear preferable [12,15,17]. In particular, for advanced skills that have had no improvement in WST results (e.g., perform a stationary wheelie) along with the complexity of the dance activity integrating wheelchair skills, to allow more time for rest between training sessions and consolidation or to vary contexts in which wheelchair skills are practiced could be beneficial to improve dance camp [15,17].…”
Section: Masterymentioning
confidence: 99%
See 3 more Smart Citations
“…The team chose to conduct an intensive dance camp because several studies suggest that intensive rehabilitative approaches (with intense repetitions) are associated with improved neuroplasticity and global motor function over the long term [18,39,40]. Even though the most optimal duration and frequency remain unknown for young people, some research suggests that condensed training may not be the most suitable option to promote skills development in this population and that, consequently, frequent and shorter training sessions distributed over a longer period of time appear preferable [12,15,17]. In particular, for advanced skills that have had no improvement in WST results (e.g., perform a stationary wheelie) along with the complexity of the dance activity integrating wheelchair skills, to allow more time for rest between training sessions and consolidation or to vary contexts in which wheelchair skills are practiced could be beneficial to improve dance camp [15,17].…”
Section: Masterymentioning
confidence: 99%
“…Even though the most optimal duration and frequency remain unknown for young people, some research suggests that condensed training may not be the most suitable option to promote skills development in this population and that, consequently, frequent and shorter training sessions distributed over a longer period of time appear preferable [12,15,17]. In particular, for advanced skills that have had no improvement in WST results (e.g., perform a stationary wheelie) along with the complexity of the dance activity integrating wheelchair skills, to allow more time for rest between training sessions and consolidation or to vary contexts in which wheelchair skills are practiced could be beneficial to improve dance camp [15,17]. Further studies would be needed to determine whether intensive therapy is more effective than conventional therapy when interventions are distributed over a longer period of time [41].…”
Section: Masterymentioning
confidence: 99%
See 2 more Smart Citations
“…A further example for the effectiveness and importance of communitybased rehabilitation comes from a 2019 study by Madsen et al (2020) They reviewed nine articles on outdoor and communitybased rehabilitation programs and reached the conclusion that the programs "seemed to empower participation opportunities and social inclusion of people with disabilities" (Madsen et al, 2020). Additional support comes from a 2022 pilot study that assessed 8 wheelchair participants and found that "a community-based peerled approach to wheelchair skills training seems promising for improving wheelchair outcomes" (Ouellet et al, 2022).…”
Section: Community/peer-based Programsmentioning
confidence: 99%